KONTRIBUSI KOMITMEN GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU PENELITIAN KORELASIONAL DI MADRASAH ALIYAH NEGERI 2 BATUSANGKAR KABUPATEN TANAH DATAR - Irnawati Irnawati (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This correlational study was aimed at revealing the contribution of teachers’ commitment and school leadership to the teachers’ discipline at State Islamic High School (MAN) 2 Batusangkar. The results showed that 1) the teachers’ commitment contributed to the teachers’ discipline 62.8%. It means that the teachers' commitment needs to be improved; 2) the principal's leadership contributed significantly to the teachers’ discipline 50.4%. It means that the contribution of school leadership needs to be improved; and 3) the teachers’ commitment and school leadership together significantly contributed to the teachers’ discipline 77.5% and 22.5% were influenced by other variables, it was not examined in this study. Keywords: Teachers’ Commitment, Principal Leadership and Teachers’ discipline